Characterization of the synergistic effect of fungal isolates in suppressing Ganoderma boninense and enhancing oil palm growth - Anuar, Muhammad Salahudin Kheirel; Hashim, Amalia Mohd; Sundram, Shamala; Rahman, Siti Rahmah Abdul; Ho, Chai Ling; Wong, Mui-Yun; Saidi, Noor Baity; Wasoh, Helmi; Yusof, Mohd Termizi (John Wiley and Sons, 2024)
The globally vital oil palm, a major oil producer, confronts productivity challenges due to Ganoderma boninense (Gb), causing output decline. Chemical control efforts have proven ineffective, prompting exploration of microbial-based biocontrol. While single fungal biocontrol research exists, the impact of employing multiple biocontrols concurrently to combat Ganoderma and enhance oil palm growth remains uncharted. This study examined four soil-derived fungal isolates for their ability to antagonize Gb PER71 in vitro. Molecular identification categorized them as Talaromyces spp. and Penicillium sp. Moreover, all isolates were revealed to have at least three plant growth-promoting (PGP) traits and were shown to have phosphoric hydrolase, ester hydrolase, peptide hydrolase, and glycosidase activities which are essential for plant growth. Furthermore, the synergistic evaluation of fungal isolates was tested against Gb PER71. One out of six combinations of fungal isolates showed a synergistic effect in vitro, and two showed a synergistic effect in planta. The application of single and combined fungal isolates tested in planta also suppressed Gb PER71 and enhanced oil palm growth compared to control groups. The findings indicate the promising potential of these isolates as biocontrol agents (BCAs) and bioformulations against Gb in oil palm cultivation.